Typhoon Risk Analysis of Offshore Wind Farms - Kaneko, Masahiko; Fukushima, Seiichiro; ICASP14; Shinohara, Mizuki; Hayashi, Takayuki (My University, 2023)
Motivation of the research Recently in Japan, offshore wind power generation has drawn attention in realizing decarbonized society, followed by the many projects of the offshore wind power generation are promoted throughout the country. To construct the offshore wind farm around Japan islands it is important to cope with the Japan-specific environmental problems and natural disasters. Although the methods such as risk financing or risk control are necessary to take countermeasures against natural disasters in advance, the minute risk analysis methods for the natural disaster risk in Japan have not been established. In response to this, authors examine the typhoon risk analysis method for offshore wind farms. Outline of the proposed method Offshore wind farms are large systems consisting of many components, so that the event tree analysis is employed to consider the disaster of components comprehensively. For example, the branches in the tree are, loss of pitch control, damage to supporting system and damage to RNA assembly. It is noted that the branches consist of sub-branches. Probability of each branch probability is given from corresponding fragility curve developed in this study. The index of the fragility curve is the 10-minute averaged wind speed at the height of 20m above sea level. Two types of consequences, such as production cost and installation cost are assigned for resulting 448 end branches based on the current realistic estimation. The relationship between the wind speed and weighted sum of the consequence is obtained as the damage function of the offshore wind farm. Application of the method. The typhoon hazard is evaluated by Monte-Carlo simulation of generating sample typhoons. For each sample typhoon, estimated is the distribution of barometric pressure, by which gradient wind is calculated using Ishiharaﾒs formula. Then, the 0-minute averaged wind speed at the height of 20m above sea level is estimated using nonlinear wind condition anticipating model MASCOT. Model sites consisting of plural windmills are divided into some blocks to express the partial correlation of damages to the facilities. This correlation is expressed also by the event tree so that the numerous numbers of branches are generated. It is noted that the size of windmill and type of foundation are considered as the parameters of the analysis. As the result of the application, the risk curves that are the relationship between the damage cost and its annual exceedance probability are obtained.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED